Analysis on the Influence Degree of Deformation Control Factors of Deep-Buried Roadway’s Fractured Surrounding Rock Using Orthogonal Design - Ke Li; Weijian Yu; Youlin Xu; Ze Zhou; Mengtang Xu; Wei Liang (Advances in Civil Engineering)
It is a complex issue to select the support structure parameters for a deep-buried roadway with fractured surrounding rock; especially when the support structure parameters need to be adjusted, the influence degree of support structure parameters on roadway deformation needs to be determined. The deformation of deep-buried roadway’s fractured surrounding rock development was investigated using multi-index orthoplan in this paper. According to the coal mine field investigation, support structure’s failure often occurs, and some need to be repaired many times. Through the roadway surrounding rock drilling, it was found that the stress of the surrounding rock was relieved, resulting in the cavity and separation of the stratum layer. The two sidewalls’ development and roof fractures are mainly tangential, and the original rock state appears only beyond 6.3∼8.2 m. The length of bolts, the row distance between bolts, the length of cables, and the row distance of U-shaped steel were selected as control factors in the multi-index orthogonal design, and roadway’s deformation values were taken as the test indexes. According to the orthoplan, nine numerical simulation schemes were designed, and FLAC3D was used for establishment. The range analysis method was used to analyze the test results. The results show that the control factors’ influence order on the total deformation of the roadway is as follows: row spacing between U-shaped steel > bolt length > cable length > row spacing between bolts, the influence order on the deformation of the roadway floor is as follows: row spacing between U-shaped steel > row spacing between bolts > bolt length > cable length, same as the left sidewall and right sidewall, and the influence order on the roadway roof’s deformation is as follows: row spacing between U-shaped steel > bolt length = cable length > row spacing between bolts, which provide a reference for the support design of deep-buried roadways with fractured surrounding rock, especially the adjustment of the supporting structure.